Evaluating the Ionospheric Mass Source for Jupiter's Magnetosphere: An Ionospheric Outflow Model for the Auroral Regions. Issue 7 (16th July 2020) - Martin, C. J.; Ray, L. C.; Constable, D. A.; Southwood, D. J.; Lorch, C. T. S.; Felici, M.
Abstract: Ionospheric outflow is the flow of plasma initiated by a loss of equilibrium along a magnetic field line, which induces an ambipolar electric field due to the separation of electrons and ions in a gravitational field and other mass‐dependent sources. We have developed an ionospheric outflow model using the transport equations to determine the number of particles that flow into the outer magnetosphere of Jupiter. The model ranges from 1, 400 km in altitude above the 1 bar level to 2.5 RJ along the magnetic field line and considers H + and H 3 + as the main ion constituents. Previously, only pressure gradients and gravitational forces were considered in modeling polar wind. However, at Jupiter we need to evaluate the effect of field‐aligned currents present in the auroral regions due to the breakdown of corotation in the magnetosphere, along with the centrifugal force exerted on the particles due to the fast planetary rotation rate. The total number flux from both hemispheres is found to be 1.3–1.8 × 10 28 s −1 comparable in total number flux to the Io plasma source. The mass flux is lower due to the difference in ion species. This influx of protons from the ionosphere into the inner and middle magnetosphere needs to be included in future assessments of global flux tube dynamics and composition of the magnetosphere system. Key Points: An ionospheric outflow model is developed for use at Jupiter's auroral regions The model evaluates the effect of field‐aligned currents and centrifugal forces A total number flux of 1.3 – 1.8 × 10 28 s −1 is found, which is comparable to number flux from Io